Design Analysis of Mountoya Bottled Water - Elin Herlina (Universitas Kuningan, 2019)
Bottled drinking water products are exclusive goods because those who consume are usually important guests from abroad. In the early 1970s, bottled drinking water had not yet existed in Indonesia. In the 1970s if there were imported products, tourists at that time only wanted to consume bottled water because they didn't match the boiled drinking water. PT. Toyamilindo Cirebon is a company engaged in the bottled drinking water industry which has a packaging brand with the Mountoya brand. Mountoya bottled mineral water packaging that is produced now, no longer uses plastic labels as a product identifier. Mountoya does not use a plastic label replaced with embossed writing on the bottle. This plain bottle is a concern that attracts consumers. This research wants to know the packaging design that is in the Mountoya bottle. In addition, the visual appeal and practical appeal in Mountoya bottle packaging is also a special attraction. The results of this study are the design of Mountoya bottle packaging in the product description is quite complete, the product description in the use of the type of plastic used is suitable for food and can be recycled. In addition there are halal information, Indonesian national standards and other full product information.